Effect of oscillatory shear field on the morphology and mechanical properties of β‐nucleated isotactic polypropylene. Issue 8 (7th November 2016) - Luo, Xiehuai; Pan, Yuxi; Li, Yongchao; Gao, Xueqin; Lei, Jun; An, Fangzhen; Li, Zhongming; Shen, Kaizhi
Abstract : The aim of this study is to investigate the effects of extra oscillatory shear field on morphology and mechanical properties of β‐nucleated isotactic polypropylene by using a homemade vibration‐assisted extrusion apparatus, in which oscillatory shear field was introduced into the extrusion head driven by crank and link mechanism. The results show that the extra oscillatory shear filed induces a significantly enhanced orientation of β‐crystal besides causing a better homogeneous dispersion of β‐nucleant, and the oriented β‐crystal has a high ratio of daughter lamellae to parent lamellae orientation, which was rarely reported in other literatures. The vibration increased the overall crystallinity and changed the relative content of β‐crystal. For the higher level nucleation agent content iPP(0.4 wt%), the relative contents of β‐crystal just changed a little or basically unchanged after vibration. However, for iPP contenting 0.2 wt% nucleation agent, the content of β‐crystal decreased. All the changes in the morphology, crystallinity, dispersion of β‐nucleant and β‐crystal content had a great influence on the mechanical properties, and that result was the improvement of yield stress and decrement of the elongation at break. POLYM. ENG. SCI., 57:838–845, 2017. © 2016 Society of Plastics Engineers